Demographic Profiling of South African Young Adults in Relation to Post-Traumatic Stress Symptomatology - Mayet, Safiyyah (University of the Witwatersrand, Johannesburg, 2025)
Post-Traumatic Stress Symptomatology (PTSS) among young adults in South Africa remains an understudied area despite the country's high exposure to trauma. This study examines the prevalence of PTSS and its associations with key demographic factors, including gender, home language, socioeconomic status, and religious beliefs. Utilising secondary data from the Africa Long Life Study (ALLS), a quantitative, non-experimental, and cross-sectional design was employed. A total of 819 participants were recruited through convenience and snowball sampling. The International Mental Health Assessment (IMHA) was used to assess PTSS, while socioeconomic status and religiosity were measured using the Family Affluence Scale (FAS) and the Duke Religion Index (DUREL), respectively. Descriptive statistics and inferential analyses were conducted. Correlation analyses, t-tests, and ANOVA tests were employed to determine the relationships between demographic variables and PTSS. Results indicated that PTSS prevalence was low within the sample, with significant variations observed across gender and socioeconomic groups. Females reported higher levels of PTSS compared to males, and individuals with lower socioeconomic status exhibited heightened PTSS. Religious involvement, particularly organisational religious activity, demonstrated a protective effect against PTSS. However, home language did not show a statistically significant association with PTSS. These findings underscore the importance of targeted mental health interventions, particularly for socioeconomically disadvantaged groups and young women. The study contributes to the broader discourse on trauma and mental health in emerging adulthood within the South African context.
A research report submitted in fulfillment of the requirements for the Master of Arts in Clinical Psychology, in the Faculty of Humanities, School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2025
Keywords: UCTD; Post-Traumatic Stress Symptomatology; Emerging Adulthood; South Africa; Demographic Profiling; Mental Health; SDG-3: Good health and well-being